The palaeomagnetic field as inferred from magnetic studies on magmatic arc zones - Urrutia-Fucugauchi, J. (Geophysical Journal International, 1982)
Processes involved in the generation of arc maginatism, which are associated with the evolution of subduction zones, may in certain cases be able to record the variations of the Earth's magnetic field with time. A mechanism is suggested which may generate lineated magnetic anomaly patterns, similar to those observed over oceanic areas, with bands of alternating normal and reverse polarity parallel to the subduction zone. It is suggested that magmatic arc rocks acquire remanent magnetizations creating a zone of normal or reverse polarity in the magmatic arc zone, and if the geometric arrangement of plate subduction changes, i.e. the region of primary magma generation is displaced normal to the trench by changes of either the Wadati—Benioff zone dip angle or the trench position, then active arc magmatism is displaced accordingly, creating another magnetic anomaly zone. An important factor is the rate of displacement of arc magnatism with time; estimates for the south-western North America magmatic arc gives a value of about 1.2 cm yr−1 for the interval 100–55 Myr ago, which is comparable to sea-floor spreading rates. The elongated patterns of positive and negative magnetic anomalies, trenchward of the Japan trench and the Kurile—Kamchatka trench may have been produced by this process. Elongated intense magnetic anomalies are also observed in other magmatic arc assemblages, such as in western North America. Processes which may obscure these lineated anomaly patterns include, e.g. tectomc rotations within the magmatic arc zone, changes in thermal conditions and igneous activity, remagnetization events and decay of remanent magnetism. The anomalies may be related to, and better preserved by, intrusive rocks or buried rocks.